Examining the efffects of university teacher self-efficacy on job satisfaction facing OMO teaching during post Covid-19 pandemic - Jin, Ying; Che Hassan, Norlizah (Human Resource Management Academic Research Society, 2022)
Teachers' self-efficacy and teachers' job satisfaction are important factors to stimulate teachers' work motivation, and also decisive factors to improve the quality of university education. This paper aims to investigate the general situation of university Teachers' self-efficacy and teachers' job satisfaction, and further explore the relationship between College Teachers' self-efficacy and teachers' job satisfaction. This paper adopts quantitative research method, using teacher job satisfaction questionnaire (JSQ) and teacher efficacy questionnaire(TSQ). Using SPSS to analyze the data, the reliability values obtained by retest technique were 0.78 and 0.73 respectively. Data collected were analyzed using inferential statistics, T-test and analysis of variance were used to test these three hypotheses. These assumptions have a significance level of 0.05. The research shows that there are significant differences in teachers' self-efficacy in professional title, educational background and subjects, and there are also significant differences in Teachers' job satisfaction in professional title, educational background and subjects. The data show that there is a significant positive relationship between job satisfaction and self-efficacy of university teachers. The study further shows that high self-efficacy of university teachers will have higher job satisfaction. The conclusion of the study shows that university should strengthen the humanistic care of teachers, so that teachers can have a better development platform, generate high teacher self-efficacy, and then improve the job satisfaction of university teachers, thus improving the quality of university education.